2020
DOI: 10.1126/sciadv.aax9914
|View full text |Cite
|
Sign up to set email alerts
|

IRE1α kinase–mediated unconventional protein secretion rescues misfolded CFTR and pendrin

Abstract: The most prevalent pathogenic mutations in the CFTR (ΔF508) and SLC26A4/pendrin (p.H723R), which cause cystic fibrosis and congenital hearing loss, respectively, evoke protein misfolding and subsequent defects in their cell surface trafficking. Here, we report that activation of the IRE1α kinase pathway can rescue the cell surface expression of ΔF508-CFTR and p.H723R-pendrin through a Golgi-independent unconventional protein secretion (UPS) route. In mammalian cells, inhibition of IRE1α kinase, but not inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…The UPS process is generally activated under cellular stress conditions and is considered part of the cellular stress response ( Kim et al, 2018 ; Park et al, 2020 ). Similarly, autophagy is also triggered by various cellular stress-inducing stimuli, so that the UPS and autophagy processes may share many common traits with significant overlap.…”
Section: Introductionmentioning
confidence: 99%
“…The UPS process is generally activated under cellular stress conditions and is considered part of the cellular stress response ( Kim et al, 2018 ; Park et al, 2020 ). Similarly, autophagy is also triggered by various cellular stress-inducing stimuli, so that the UPS and autophagy processes may share many common traits with significant overlap.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, upregulation of UPS pathways resulting from GRASP55 overexpression or IRE1𝛼 kinase activation has been shown to directly induce the cell surface expression of the ER form of coreglycosylated CFTR and pendrin, bypassing the Golgi, suggesting that UPS activation could be a strategy to treat diseases caused by trafficking-defective CFTR and pendrin. [4,6] Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is the etiologic agent of COVID-19 and belongs to the genus 𝛽-coronavirus (group 2). [13] The spike (S) protein is an Nglycosylated transmembrane protein and class I fusion protein in the viral envelope, which plays a critical role in the infection of host cells.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 , 2 , 3 ] In particular, under blocked ER‐to‐Golgi transport or ER stress conditions, misfolded cystic fibrosis transmembrane conductance regulator (CFTR) and pendrin proteins, which are responsible for cystic fibrosis (CF) and specialized forms of congenital hearing loss (Pendred syndrome and DFNB4), respectively, can reach the plasma membrane via a Golgi‐independent UPS route. [ 4 , 5 ] Although several factors such as Golgi reassembly‐stacking proteins (GRASPs) and inositol‐requiring enzyme 1α (IRE1α) kinase cascades have been shown to be involved, [ 4 , 6 ] the molecular mechanisms underlying ER stress‐associated protein secretion, including the sorting determinants for how UPS substrates are selected, remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that under blocked ER-to-Golgi transport or ER stress conditions, immature core-glycosylated CFTR and pendrin can reach the plasma membrane via the Golgi-bypass UPS pathway and retain their anion transporting activity. The basic mechanisms by which these two proteins reach the cell membrane via UPS appear to be similar, both enhanced by IRE1α kinase pathway activation ( Park et al, 2020 ). However, some key molecules controlling the UPS of these two membrane proteins are not identical.…”
Section: Introductionmentioning
confidence: 99%